Memoirs of a geisha - Zhang, Ziyi, 1979-; Yeoh, Michelle, 1963-; Watanabe, Ken, 1959-; Golden, Arthur, 1957; Marshall, Rob; Fisher, Lucy; Spielberg, Steven; Wick, Douglas (Culver City, Calif. : Sony Pictures Home Entertainment, 2006)
Set in 1930's Japan, a young girl who is sold to a geisha house works her way up to become one of the most desirable geishas of her time
Based on the novel by Arthur Golden
Title from title screen
Disc 1 is movie, disc 2 is features that contains Sayuri's journey, the road to Japan, Geisha bootcamp, building the Hanamachi, the look of a Geisha, the music of memoirs, a Geisha's dance, the world of the Geisha, the way of the Sumo, director Rob Marshall's story, a day with chef Nobu Matsuhisa and photo gallery
Subtitles in Malay, Chinese and English
Executive producer, Roger Birnbaum...[et al.] ; screenplay by Robin Swicord ; music, John Williams ; editor, Petro Scalia
Cast : Ziyi Zhang, Michelle Yeoh, Ken Watanabe, Suzuka Ohgo, Li Gong
Keywords: Golden, Arthur, -- 1957- -- Film and video adaptations; Geishas -- Japan -- Drama; World War, 1939-1945 -- Japan -- Drama; Japan -- Drama